The role of the sign form of science in realizing the goals of teaching physics (Journal of Educational Sciences, 2022)
The article is devoted to the use of intersubject connections, methods of consolidation of didactic units and analogies in the professional training of a physics teacher. Intersubject relations are considered based on the analysis of laws and formulas from various sections of physics, analysis of various problem situations. Attention is drawn to the role of the sign-symbolic form in revealing the unity of the laws of nature that determine various physical phenomena. The method of enlarging didactic units of P. M. Erdniev allows to combine various physical phenomena into one such unit and to reveal the commonality of their laws. The attention of students is drawn to the ability to determine the analytical relationships of physical quantities based on the given graphs. Important in the content of physics are research of situations with parallel or serial connection of homogeneous elements: springs of capacitors, resistors, inductors, current sources. Analysis of such connections in a single didactic unit allows you to see the role of different characteristics of physical objects, find analogies between them and think about why the law of sequential connection of some characteristics corresponds to the law of parallel connection of other characteristics. Attention to the analysis of the sign form of the content of physical phenomena contributes to a deeper assimilation of the subject of study.The developed teaching methodology integrated three didactic principles: (1) interdisciplinary links between physics and mathematics, (2) enlargement of didactic units, (3) visualization of physics teaching with demonstration of laws and analogies in the laws of physics and mathematics in sign and symbol form. The principle of visual demonstration for students and schoolchildren is actualized by the modern thinking of the digital generation. Fifty-six physics teachers from schools across the country responded to the practical part of the study. It was found that 66.1% of them actively use tasks with conditions in the form of drawings, 30.4% - use rarely. According to the evaluation of 55.4% of teachers of the sample, students often have difficulties in solving problems with graphical representation of conditions and requiring graphical answers; 78.6% of teachers emphasize the interdisciplinary links between physics and mathematics. The survey results show the relevance of developing such a teaching methodology.Keywords: physical science; mathematical apparatus; sign form of content; analytical and graphical methods; functional dependence; resistance; electrical capacity; stiffness; parallel and serial connections; problem situations.